2021
DOI: 10.1007/s13300-021-01145-4
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Verapamil on TXNIP Gene Expression, GLP1R mRNA, FBS, HbA1c, and Lipid Profile in T2DM Patients Receiving Metformin and Sitagliptin

Abstract: Introduction Type 2 diabetes mellitus (T2DM) is the most common type of diabetes. A decrease in the number of pancreatic beta cells is a pathological sign of diabetes, and to date there is no drug treatment that targets damage to these cells. Pancreatic beta cells have a weak antioxidant system and are highly sensitive to oxidative stress reactions that occur within cells. Thioredoxin interacting protein (TXNIP) inhibits thioredoxin, which is part of the intracellular antioxidant system, thereby a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 34 publications
2
5
0
Order By: Relevance
“…In this regard, insulin represents the main player for promotion and maintenance of metabolism [32]. In the scientific community it is an accepted fact that diabetes is associated with a reduction in β-cell mass and to date there is no approved drug treatment that targets damage to these cells [33,34]. Pancreatic β-cells have, as reported in several studies, a weak antioxidant capacity and are very sensitive to oxidative stress interactions occurring within the cells [31,33].…”
Section: Methods Section Scientific Researchmentioning
confidence: 99%
See 3 more Smart Citations
“…In this regard, insulin represents the main player for promotion and maintenance of metabolism [32]. In the scientific community it is an accepted fact that diabetes is associated with a reduction in β-cell mass and to date there is no approved drug treatment that targets damage to these cells [33,34]. Pancreatic β-cells have, as reported in several studies, a weak antioxidant capacity and are very sensitive to oxidative stress interactions occurring within the cells [31,33].…”
Section: Methods Section Scientific Researchmentioning
confidence: 99%
“…In the scientific community it is an accepted fact that diabetes is associated with a reduction in β-cell mass and to date there is no approved drug treatment that targets damage to these cells [33,34]. Pancreatic β-cells have, as reported in several studies, a weak antioxidant capacity and are very sensitive to oxidative stress interactions occurring within the cells [31,33]. Although several trials have studied the mechanisms of β-cell loss in the different types of diabetes, there is less information referring to the residual β-cells in autoimmune T1D [35].…”
Section: Methods Section Scientific Researchmentioning
confidence: 99%
See 2 more Smart Citations
“…To investigate this annotation, an elegant study was conducted by Malayeri et al, who evaluated the efficacy and safety of oral verapamil in patients with T2D. This randomized, double-blind, placebo-controlled clinical trial showed a significant reduction in Hb1Ac levels in patients with T2D, following treatment with verapamil ( Malayeri et al, 2021 ). It is noteworthy that co-treatment with verapamil and metformin significantly improved the glycemic control in patients with T2D by reducing HbA1c and fasting plasma glucose levels ( Wang et al, 2022 ).…”
Section: From Hypertension To Diabetes Mellitusmentioning
confidence: 99%